Implementation of a V/f Controlled Variable Speed Induction Motor Drive - Duranay, Zeynep Bala; Guldemir, Hanifi; Tuncer, Servet (Politeknik Elektronika Negeri Surabaya, 2020)
DSP implementation of speed control of three phase induction motor drive is presented in this paper. A closed loop speed control has been achieved using constant V/f technique which is a simple scalar control method used to control the magnitude of the control quantities. In this study, a fourth order polynomial drived from V/f curve is constructed instead of using look up table which takes much time for determination of voltage from frequency value. A PI controller is used in speed control. dSPACE DS-1103 controller board is used for the implementation with Matlab/Simulink, which has a simple real time interface. Steady-state speed characteristics and transient responses with various reference speed commands are presented by experimental system. The simulation and experimental results provide a smooth speed response and good performance under various dynamic operations. Real time speed control has been implemented and some results are presented.
Keywords: frequency control; induction motors; motor drives; speed control; variable speed drive